Social Capital in Building Regional Innovative Capability: A Theoretical and Conceptual Assessment - Tomi Tura; Vesa Harmaakorpi (European Regional Science Association (ERSA), 2003)
Innovative capability is widely seen to be the driving force in building regional competitive advantage. The present paradigm emphasises the interactive nature of the innovative processes, which sets demands on building regional innovation environment. There are certain theoretical frameworks and concepts that are considered to help in analysing the creation of regional innovative capability in the present networked development environment: social capital, regional innovation system, innovative milieu, learning economy, network leadership, creative tension, etc. These concepts are partly overlapping, but each of them gives different contribution for regional development strategies. Regional innovative capability is understood as firms' and other organisations' common innovative capability in a region. Therefore, it is formed of innovative capability of individual actors and innovation networks taking part in the regional innovation system. This combined innovative capability is, at its best, a lot more than the sum of individual parts of the system, mainly because of the achieved externalities in the networks. Network skills of the actors and mutual trust among the actors are often emphasised as assets for regional innovative capability, especially because of the often complex nature of multi-actor, interactive innovative processes. The concept of social capital is gaining importance in regional research. The concept has no commonly accepted definition, but usually it is understood as a specific form of capital, that is derived from social relations, norms, values and interaction within a community. Trust is often considered to the most important social mechanism creating social capital. It is widely accepted that social capital plays an important role in creating regional innovative capability. However, it is still far from clear what this role exactly is, and its relation to other relevant concepts has not been deeply examined. The current article is an attempt to clarify the conceptual framework related to the concept of social capital in the context of regional development. Another focus of the article is set on assessing the special contribution of social capital (in comparison with the other related concepts) in increasing regional innovative capability. Therefore, the main objectives of the article are: - to analyse the concept of social capital and its relation to other relevant concepts in the context of regional development, and - to explain the role of social capital in building regional innovative capability. A regional innovation system is essentially an unstable field of actors: their values, interests and purposes may differ significantly. Therefore, social capital cannot be based solely on shared values and purposes. We will argue that social capital is best understood as a formation of resources embedded in the social relations of the network. These resources can have their origin in the structural constitution of the network, trust-based relations between actors, or cognitive and emotional commitments to common goals or beliefs. This conception leads us to understand that social capital may play various different roles in the creation of regional innovative capability.
Keywords: 330